ANALYSIS OF GOVERNMENT EXPENDITURE, NATIONAL INCOME LEVEL AND HOUSEHOLD ELECTRICITY PRICES ON ENERGY POVERTY IN INDONESIA - Nuzaimah; Jariah Abubakar (RADJA PUBLIKA, 2025)
The purpose of this study is to determine the Influence of government spending, national income level and household electricity prices on energy poverty in Indonesia. The study uses Time Series data from 1970-2023. The study uses the Autoregressive Distributed Lag (ARDL) method.The results of the short-term and long term study show that the of government spending have a negative and significant effect on energy poverty in Indonesia, national income levels have a positive and significant effect on energy poverty in Indonesia, and the household electricity prices have a negative and significant effect on energy poverty in Indonesia. In the long term, the household electricity prices have a negative and significant effect on energy poverty in Indonesia.